Embodied energy of service trading in Hong Kong. Issue 2 (21st September 2015) - Geoffrey Shen, Professor; Guo, Shan; Shen, Geoffrey; Yang, Jay; Sun, Bingxia; Xue, Fan
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Energy is a resource of strategic importance for high density cities. International trade reshapes the urban economy and industrial structure of a city, which will indirectly affect energy use. As an international trade hub, Hong Kong relies on the import and export of services. Energy performance in the international trading of these services needs to be properly understood and assessed for Hong Kong's urban renewal efforts. The paper aims to discuss these issues. Design/methodology/approach – This study evaluates Hong Kong's embodied energy in service trades based on an input-output analysis. The three criteria used for assessment include trading areas, industry sector and trade balance. Findings – Analyzed by region, results show that Mainland China and the USA are the two largest sources of embodied energy in imports of services, while Mainland China and Japan are the two largest destinations of exports. In terms of net embodied energy transfer, Hong Kong mainly receives net energy import from Mainland China and the USA and supplies net energy export to Japan, the UK and Taiwan. Among industry sectors, manufacturing services, transport and travel contribute most significantly to the embodied energy in Hong Kong's imported services, while transport and travel contribute most to the energy embodied in exported services. Originality/value – This study identifies the characteristics of energy consumption of service trading and establishes a feasible approach to analyze energy performance of service trade in energy-deficient Hong Kong for the first time. It provides necessary understanding and foundation for developing energy strategies in a service-based, high density urban economy.